The DEXA-CORT trial: study protocol of a randomised placebo-controlled trial of hydrocortisone in patients with brain tumour on the prevention of neuropsychiatric adverse effects caused by perioperative dexamethasone - Elisabeth F C van Rossum; Amir H Zamanipoor Najafabadi; Wouter A Moojen; Nienke R Biermasz; Wouter R van Furth; Onno C Meijer; Clemens M F Dirven; Anne-Sophie C A M Koning; Djaina D Satoer; Christiaan H Vinkers; Rishi D S Nandoe Tewarie; Alberto M Pereira (BMJ Open)
Introduction The synthetic glucocorticoid dexamethasone can induce serious neuropsychiatric adverse effects. Dexamethasone activates the glucocorticoid receptor (GR) but, unlike endogenous cortisol, not the mineralocorticoid receptor (MR). Moreover, dexamethasone suppresses cortisol production, thereby eliminating its MR binding. Consequently, GR overactivation combined with MR underactivation may contribute to the neuropsychiatric adverse effects of dexamethasone. The DEXA-CORT trial aims to reactivate the MR using cortisol to reduce neuropsychiatric adverse effects of dexamethasone treatment.Methods and analysis The DEXA-CORT study is a multicentre, randomised, double-blind, placebo-controlled trial in adult patients who undergo elective brain tumour resection treated perioperatively with high doses of dexamethasone to minimise cerebral oedema. 180 patients are randomised between treatment with either two times per day 10 mg hydrocortisone or placebo during dexamethasone treatment. The primary study outcome is the difference in proportion of patients scoring ≥3 points on at least one of the Brief Psychiatric Rating Scale (BPRS) questions 5 days postoperatively or earlier at discharge. Secondary outcomes are neuropsychiatric symptoms, quality of sleep, health-related quality of life and neurocognitive functioning at several time points postoperatively. Furthermore, neuropsychiatric history, serious adverse events, prescribed (psychiatric) medication and referrals or evaluations of psychiatrist/psychologist and laboratory measurements are assessed.Ethics and dissemination The study protocol has been approved by the Medical Research Ethics Committee of the Leiden University Medical Center, and by the Dutch competent authority, and by the Institutional Review Boards of the participating sites. It is an investigator-initiated study with financial support by The Netherlands Organisation for Health Research and Development (ZonMw) and the Dutch Brain Foundation. Results of the study will be submitted for publication in a peer-reviewed journal.Trial registration number NL6726 (Netherlands Trial Register); open for patient inclusion. EudraCT number 2017-003705-17.